Organic Farming in Animal Husbandry Practices - Patel, S. J.; Kumar, Upesh; Chaudhari, R. P; Darji, S. S (Indian Journal of Hill Farming, 2018)
Organic animal husbandry deliberately avoids the use of synthetic inputs such as drugs, feed additives and genetically engineered breeding inputs. Organic livestock farming differs from conventional farming where, livestock essentially integrated with crop farming under subsistence farming operations with low input low output production systems. The standards for organic production are basic requirement. Organic livestock production requires producers to establish preventive health care practices. Management in organic system should be based on correct understanding of animal behavior. In developed countries, organic regulations are increasingly requiring that animals should be raised on pasture. Developing nations seek to export organic products or conventional products, they will still need to evolve acceptable traceability mechanisms. Better animal health conditions are needed, especially in the case of organic livestock production. If we are to harness the potential benefits of organic farming, then training in organic production practices for both organic trainers/advisers and farmers is essential. The 'organic' is more or less a symbol of' purity and best quality of food products especially when it is certified by the recognized certification agencies. The ICAR has also recognized it as a system of agricultural production worth promotion in certain regions having potential for organic farming.